Effectiveness of peers in delivering programs or motivating older people to increase their participation in physical activity: Systematic review and meta-analysis. Issue 6 (19th March 2018) - Burton, Elissa; Farrier, Kaela; Hill, Keith D.; Codde, Jim; Airey, Phil; Hill, Anne-Marie
ABSTRACT: The objective of this systematic review and meta-analysis was to evaluate the effectiveness of peers to deliver programs or encourage older people to be physically active and improve physical outcomes. Peer reviewed articles published in English between January 1976 and June 2016, retrieved from six databases according to the predefined inclusion criteria were included. Where possible results were pooled and meta-analyses conducted. Eighteen articles were included in the review, a total of 3, 492 intervention participants, average age 66.5 years and 67.1% were female. Overall, study quality was medium to high. Interventions mainly included resistance, flexibility and cardiovascular training, however there was one aquatic exercise group. Eight studies were delivered by peers and five utilised peer support, which included advice and being positive but was not directly linked to an exercise intervention. While 16 of the 18 studies reported improvement in levels of physical activity and/or noted physical benefits by peer involvement, the meta-analyses findings supported the control groups for the six-minute-walk-test and the timed-up-and-go test. Findings from this review suggest exercise programs involving peers can promote and maintain adherence to exercise programs. However, results were inconclusive as to whether peers have a positive effect on improving older people's physical function.